Ethnomedical uses and pharmacological activities of most prevalent species of genus Piper in Panama: A review. (10th May 2018) - Durant-Archibold, Armando A.; Santana, Ana I.; Gupta, Mahabir P.
Abstract: Ethnopharmacological relevance: Piperaceae is the fifth largest family of plants in Panama. This review focuses on the ethnomedical uses of the most prevalent Panamanian species and biological activities of their extracts and/or constituents both in Panama and worldwide. Many species have a plethora of ethnomedical uses such as antibacterial, antifungal, anti-inflammatory, anticancer, antidiabetic, anti- Helicobacter pylori, antiulcer, antiprotozoal, estrogenic, insecticidal, local anesthetic, diuretic, and for women's health conditions. Aim of the review: The aim of this review is to compile all ethnomedical uses of most prevalent species of Piper in Panama, and their extracts or phytoconstituents worldwide, through a complete literature search, so that it may allow selection of potential unexplored Piper species for future research and development of phytotherapeuticals for important ailments. Methodology: This review conducted a thorough search in books and databases such as Google Scholar, PubMed, Sci-Finder, Scopus, ACS publications, Science Direct, and Reaxys (Elsevier), until October of 2017. The information provided in this review is based on peer-reviewed papers only in English. The key words used to search were: " Piper ", "Piperaceae", "Panama", "Pharmacological activity", "Chemistry, " "Toxicity, " and "Clinical studies". Scientific names of the plants were validated throughwww.tropicos.org . Potential full-texts of eligible papers, irrespective of database, were identified. Study selection and data extraction were conducted by one author (AIS) and confirmed by others (MPG, ADA). The extracted data were summarized in tabular form and a narrative description was used to provide a summary of updated information. Results: The ethnomedical uses of most prevalent 23 Panamanian species of Piper both in Panama as well in the world are provided. Of these species only Piper arboreum, Piper auritum, Piper cordulatum, Piper hispidum, Piper dariense, Piper multiplinervium and Piper umbellatum have ethnomedical uses in Panama. Some of the uses are by native Amerindians of Panama. These include ailments such as liver pains, common colds, skin infections, insecticidal, as a bath to alleviate colds, snakebites, different types of pains, skin ailments, wound healing, rheumatism, women's health, antipyretic, and anti-inflammatory. Other Panamanian species are widely used in many countries of the world. Of all the Piper species, P. aduncum has the most ethnomedical uses. Panamanian uses are different from the ones in other countries. A total of 61 compounds present in Piper species reported in this review have shown a variety of biological activities in vitro. These compounds belong to different chemical types, such as chromenes, amides, alkaloids, benzopyrans, benzoates, essential oils, pyrrolidines, flavokaines, chalcones, methylenedioxy propiophenones, cinnamates, monoterpenes, sesquiterpenes, phenols, among others. From this review it is evident that extracts and pure compounds isolated from Piper species have shown a wide array of mainly in vitro activity and some ethnomedical uses may be correlated with their activities reported. Conclusions: Plants of this genus have provided bioactive species, both from crude extracts and pure compounds thus substantiating their efficacy in traditional medicine. In vivo and toxicological studies are still limited, but the results of different activities of Piper reported point out the great potential of these species for obtaining bioactive principles that may be useful in treating diseases. However, a thorough investigation of Piper species relating to chemistry, in vivo pharmacological activities, with emphasis on their mechanism of action, safety and efficacy and toxicity is warranted.